Rescate y conservación de la especie Brownea multijuga Britton & Killip (clavellín), mediante la técnica de propagación asexual, utilizando las hormonas enraizantes Ácido Naftalenacético (ANA) y Ácido Indolbutírico (AIB). - Vélez Espin, Yadira Nataly (2021)
The purpose of the research is to recover the species B. multijuga (clavellín) as it is affected by deforestation and indiscriminate logging, damaging many significant genotypes. For this reason, the objective of rescuing and conserving the species (clavellín) was established through an asexual propagation method using different hormonal concentrations of Naphthaleneacetic Acid and Indole Butyric Acid with their respective dosages of (0, 500, 1000, 1500 mgkg-1 of ANA) and (0, 500, 1000, 1500 mgkg-1 of IBA). A completely randomized design (DCA) was applied with four treatments, five repetitions and four experimental units for each repetition. The vegetative material was obtained from carnation trees in secondary forest that were selected by their phenotypic characteristics, and the seeds were collected exhaustively, noting that they are in a good state, later a pregerminative treatment was made to the seeds. Once the seedlings germinated and grew at 7 months of age, the individual cut of the apical bud was carried out, to induce the axillary buds, from which the young shoots were obtained, which were used in the research. Sand was used as a substrate for rooting the shoots, which was disinfected and neutralized in an oven for 20 minutes at 100 ° C to eliminate any pathogens. At 50 days, the best treatments for clavellín rooting were concentrations (1000 mgkg-1 of ANA + 1000 mgkg-1 of IBA and 1500 mgkg-1 of ANA + 1500 mgkg-1 of IBA). In addition, with this methodology it was possible to increase the number of individuals per plant, with this it is demonstrated that with this research the rescue and conservation of clavellín was achieved. Keywords: vegetative, axillary buds, rooting, concentration, plant hormone